Analisis Manajemen Pasca-Bencana dan Strategi Mitigasi Risiko: Studi Kasus Pemulihan Tragedi Kanjuruhan Malang - Nabil Nazhif Fikri Ahmad; Annisa Hangesti Prihaningrum; Zeni Fradita Sari; Keisya Reydi Natasya Sifa; Ratnasari Dewi Faradilla; M. Noer Falaq Al Amin; Nuh Krama Hadianto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to examine post-disaster management and identify weaknesses and strategies for mitigating the risks of the Kanjuruhan Tragedy in Malang, which occurred in 2022. This incident was a non-natural disaster, caused by a failure in event management and security systems at large public events. This study employed a qualitative approach through literature review, collecting secondary data from various journals, official reports, and other relevant sources. The findings revealed that the Kanjuruhan Tragedy was caused by several key factors, such as stadium overcapacity, the use of tear gas, and weak evacuation systems and inter-agency coordination. In post-disaster management, the government has implemented several initiatives, including medical treatment, psychosocial recovery, and policy evaluation through new regulations. However, weaknesses remain in terms of risk mitigation and accountability. Therefore, a more comprehensive mitigation strategy is needed, including strengthening regulations, improving stadium safety standards, and improving peatland management to prevent similar incidents in the future.